The Effect of Health Education on Knowledge Adolescent Girl About Early Marriage - Tria Adinda; Susilawati susilawati; Yuli Yantina; Riyanti Riyanti (Universitas Malahayati Lampung, 2023)
ABSTRACT There were 21 cases of marriage dispensation submitted to the Tanggamus Religious Court. The purpose of this research is to determine the effect of health education on adolescent girl’s knowledge about early marriage. The research used was quantitative with pre-experimental research, with a one-group pretest-posttest design. The sample technique uses proportional random sampling. The research was conducted from February to May on 85 respondents using a questionnaire which was then analyzed and presented in the form of a distribution table on characteristics and knowledge. The mean score of knowledge of adolescent girl about early marriage before health education was 72.36±13.88. While the mean score of knowledge after health education is 88.90± 8.83. Research found that there was an effect of health education on increasing knowledge of adolescent girl about early marriage.There is an effect of health education on increasing knowledge of adolescent girl about early marriage. It is hoped that State Senior High School 1 Kota Agung can take advantage of the animated video that has been provided by the School Health Effort staff and can educate students about early marriage. Keywords: Knowledge, Early Marriage, Adolescent Girl